2015 7th International Conference on Recent Advances in Space Technologies (RAST) 2015
DOI: 10.1109/rast.2015.7208370
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of CMG and FMC actuators for Nano satellite attitude control system-pyramidal configuration

Abstract: In this paper, nonlinear attitude model of a satellite with pyramid Control Moment Gyros (CMG) and other with pyramid Fluid Momentum Controller (FMC) is developed. A comparative study between pyramidal cluster of FMC and CMG is conducted. This comparison is based on simulation of attitude control system a Nano satellite with two different actuators. For comparison purposes, a sliding mode controller based on modified Rodriguez parameters is considered for attitude control system. The efficiency of maneuvers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The research results shows that the system can reduce uncertainty and suppress system chattering. Tayebi [4] proposed a fluid momentum controller (FMC) device, which includes liquid rings device for space control task about attitude. The authors revealed that the device effectively resisted interference and complete the attitude adjustment task.…”
Section: Introductionmentioning
confidence: 99%
“…The research results shows that the system can reduce uncertainty and suppress system chattering. Tayebi [4] proposed a fluid momentum controller (FMC) device, which includes liquid rings device for space control task about attitude. The authors revealed that the device effectively resisted interference and complete the attitude adjustment task.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao-wei et al (2011) improve fluidic momentum controller and improve satellite control performance and decrease satellite weight. Tayebi and Soleymani (2015) conduct a comparative study between pyramidal cluster of fluidic momentum controller (FMC) and control moment gyros (CMG). The control subsystem of use case that even fluid loop cannot decrease the satellite temperature; further studies investigated a special case (Akau et al, 1994;Sozbir et al, 2008) or different type of designing (Tsuyuki and Thunnissen, 2004;Struble et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between CMGs and fluid rings actuator for pyramid satellite was proposed by Tayebi and Soleymani (2015). The results show that required torques and damping time of two actuators are similar together.…”
Section: Introductionmentioning
confidence: 99%